2007
DOI: 10.1002/elsc.200720208
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Form Analysis of Metals and Sulfur Fractionation in Methanol‐Grown Anaerobic Granular Sludge

Abstract: This study investigates the metal and sulfur bonding form distribution in mesophilic (30 °C, pH 7) methanol‐grown anaerobic granular sludge from upflow anaerobic sludge bed reactors operating at an organic loading rate of 3.8 g CH3OH‐COD/L d. This was achieved by applying a modified Tessier sequential extraction scheme to investigate the metal bonding forms and a sequential extraction scheme for sulfur and simultaneously extracted metals to granular sludge samples of the reactors after 0, 22, 35 and 43 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…The sludge was collected from the bottom of the UASB reactor and contained total solids (TS) of 56. . The distribution of metals in the sludge was analyzed according to a modified Tessier method [17,18] (Table 1). …”
Section: Inoculummentioning
confidence: 99%
“…The sludge was collected from the bottom of the UASB reactor and contained total solids (TS) of 56. . The distribution of metals in the sludge was analyzed according to a modified Tessier method [17,18] (Table 1). …”
Section: Inoculummentioning
confidence: 99%
“…Irrespective of source, sulphur causes problems during anaerobic digestion as it is converted to hydrogen sulphide (H 2 S), either during the degradation of amino acids or through the activity of SRB [11]. In addition to the malodorous and corrosive properties of H 2 S gas, it is also toxic to microorganisms and can cause precipitation of trace elements required for microbial growth and activity [11,20,33]. Furthermore, the H 2 S formed have to be removed to meet Swedish legal requirements on vehicle fuel and to reduce negative effects on anaerobic digestion.…”
Section: Hydrogen Sulphidementioning
confidence: 99%
“…The high protein content in thin stillage also results in the release of organic sulphur as sulphides, which have various negative effects on the industrial biogas production process. These include corrosion, precipitation of trace elements, inhibition of microorganisms and consumption of organic material [mainly alcohols, volatile fatty acids (VFA) and hydrogen] that would otherwise be used for methane production [11,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Processes regulating the chemical speciation and bioavailability of trace metals are complex involving dynamic interaction of microorganisms with organic and inorganic compounds [11,12]. Laboratory and practical evidences have demonstrated that speciation and bioavailability of trace metals essential for the anaerobic digestion process are highly influenced by the chemistry of sulfur (S) [11][12][13][14][15]. The precipitation of metal sulfide phases and/or adsorption of trace metals to iron sulfide particles are considered to be the most important processes contributing to trace metal dynamics in biogas reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur K-edge XANES is a suitable method for identification and quantification of various S compounds, their oxidation states and binding forms in a sample [20,21], which allow us to follow the fate of S species during sequential extraction. Acid volatile sulfide analysis is a classical approach for measurement of the sulfide fraction reactive towards metals in anoxic samples, based on volatilization of reduced S bonded in mineral fractions, mainly FeS [12,22,23]. The method has in principal similar disadvantages as sequential extraction regarding the uncertainty in selectivity of the applied reagent for volatilization of reduced S compounds and simultaneously extracted metals [22].…”
Section: Introductionmentioning
confidence: 99%